Analysis of treatment results in vulvar cancer after surgical treatment in material of Clinical Ward of Gynecology and Obstetrics in Bytom, Poland - Urban, Andrzej; Wala, Dariusz; Miszczyk, Leszek; Suwiński, Rafał (Contemporary Oncology/Współczesna Onkologia, 2002)
Vulvar cancer is neoplasia very uncommon in oncological gynecology and till now is not well defined in solid and accurate standard of treatment. Each modification in vulvar cancer operational treatment changed the way the surgery was followed but did not cause crucial discovery in total patients recovery. Analyzing surgery treatment which we can find in literature we see a tendencies to optymalization of surgery and shortening of hospitalization period. Authors analyzed 111 cases of the surgery treatment and follow-up in patients with vulvar cancer between years 1992 and 2000, treated in Clinical Ward of Gynecology and Obstetrics in Bytom, Poland and Center of Oncology - Institute in Gliwice, Poland. Authors estimated FIGO stage of disease and type of surgery. Type of surgery and type of individual postoperative injury on hospitalization period and postoperative complications dependent on patients immobilisation period and type of surgery was also estimated. Postoperative treatment was estimated. The histopatological findings after surgery and number of lymph nodules found in surgery material. Mean time of survival was 2 years 10 month. Authors described own experiences in teleradiotherapy in 4 patients with vulvar cancer. Analysis of this data leds to the conclusion that individualisation of the surgery to the exact stage of vulvar cancer can shortens hospitalization time and percentage of postsurgery complications showing no influence on the time of survival.